READABILITY OF TEXTBOOK FOR THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Rizki Mandasari; Anni Holila Pulungan (Universitas Negeri Medan, 2016)
This research deals with the readability level of reading texts and the eighth gradestudents of junior high school. The objective of this research is to find out thereadability level of reading texts in English for junior high school textbook. Theresearcher used qualitative method in which the researcher describes thereadability level of reading texts in the textbook by using Gunning Fog IndexFormula. The text that will be analyze are 16 reading texts which are consists ofthree genres, 4 descriptive texts, 4 recount texts, and 8 narrative texts. They arethe whole reading texts in the English for junior high school textbook, publishedby Mediatama. Based on the analysis by using Gunning Fog Index Formula, fromtotal number 16 reading texts, 12 reading texts are in the very easy level, 1 text isin the standard level, and 3 texts are in the difficult level. In average, the texts arein the very easy level with score 7.3. It’s found based on the Gunning’s theory. Itis concluded that reading texts in English for junior high school textbook are notin the appropriate level for the eighth grade students of junior high school in SMPNegeri 3 Stabat.